Development and Validation of Android-Based Mobile App for Self-Controlling Excess Body Fluids in Chronic Renal Failure Patients Undergoing Hemodialysis: Original Article - Faridah, Virgianti Nur; Hidayati, Nur; Rokhman, Abdul; Saputra, Bagus Dwi; Bachri, Saiful (Babali Nursing Research, 2024)
Background: Chronic renal failure patients undergoing hemodialysis commonly experience excess fluid volume in the body. It is necessary to provide media which can be independently employed by the patients to control body fluids and prevent fluid overload. The purpose of the study is to develop an android-based application "Sabahat Dialisis", as well as conducting validity test, reliability test, and application usage tests on users. Methods: This research utilized a Research and Development (R&D) design consisting of two stages. In Stage 1, an Android-based application was developed and its validity and reliability were assessed by five experts in dialysis. Stage 2 involved conducting trials of the application with 30 chronic renal failure patients in the Dialysis Unit to evaluate its usability. Results: The application component proved to be valid (I-CVI=1) and reliable (Cronbach’s alpha=0.768). The results of the application use trial on 30 hemodialysis patients indicated that 83.3% considered the application easy to understand, the menu/features were easy to use and operate (83.4%: 86.7%), 76.7% of users were satisfied with the application, the application was useful, in accordance with the needs of hemodialysis patients, and easy to learn (90%), 86.7% were easy to operate, and 76.7% recommended the application for use in hemodialysis patients. Conclusion: Sahabat Dialisis application is valid, reliable, and usable for chronic renal failure patients undergoing hemodialysis to control fluid in the body and avoid fluid overload.